Qantum correlations in biomolecules - Vedral, V (2011)
In this paper we identify quantum entanglement, quantum discord and classical correlations as the main classes of correlations present in many body systems, such as biomolecules. We show how to witness the presene of entanglement and quantum discord. All witnesses can be accessed with simple measurements and implemented with current technology. We discuss the relationship between the speed of processing and presence of correlations and illustrate it in the case of photosynthesis and magnetoreception. © 2011 Published by Elsevier Ltd.